2003
DOI: 10.1590/s1516-35982003000800005
|View full text |Cite
|
Sign up to set email alerts
|

Perfil químico da parede celular e suas implicações na digestibilidade de Brachiaria brizantha e Brachiaria humidicola

Abstract: RESUMO -No presente trabalho foram determinadas a composição química e a digestibilidade de diversas frações de Brachiaria brizantha e Brachiaria humidicola, após 70 dias de crescimento. O delineamento experimental foi inteiramente casualizado com cinco repetições para cada espécie. As plantas coletadas foram subdivididas nas frações apical, mediana e basal para as folhas e mediana e basilar para caules, de acordo com sua localização. Foram determinadas as concentrações de fibra em detergente neutro (FDN), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
1
8
0
6
Order By: Relevance
“…Furthermore, other traits such as total dry matter (TDM) yield and seed dormancy could also be improved (Euclides et al 2010). The in situ digestibility of neutral detergent fiber of the stem and dry matter digestibility of the whole plant of B. brizantha were higher than that of B. humidicola (Brito et al 2003). These authors also reported a higher crude protein content of B. brizantha compared to B. humidicola.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, other traits such as total dry matter (TDM) yield and seed dormancy could also be improved (Euclides et al 2010). The in situ digestibility of neutral detergent fiber of the stem and dry matter digestibility of the whole plant of B. brizantha were higher than that of B. humidicola (Brito et al 2003). These authors also reported a higher crude protein content of B. brizantha compared to B. humidicola.…”
Section: Introductionmentioning
confidence: 98%
“…Entretanto, para plantas forrageiras, especialmente gramíneas, tais trabalhos são numerosos, o que possibilita determinar o valor nutricional das plantas, conforme Rodella et al (1982Rodella et al ( , 1984, Akin (1989), Wilson (1993), Jung & Allen (1995), Brito et al (1997aBrito et al ( , 1997bBrito et al ( , 1999Brito et al ( , 2003Brito et al ( , 2004, Ventrella et al (1997) e Brito & Rodella (2002).…”
Section: Introductionunclassified
“…The majority of pcoumaric acid are esterified to lignin whereas ferulic acid tends to associate with the hemicellulose fraction and may form a cross-linkage between lignin and hemicellulose [3,4]. Due to such associations, several studies have shown that these compounds potentially affect the digestibility of forages by the rumen, thereby compromising livestock performance [3,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%